Changing from a Western to a Mediterranean-style diet does not affect iron or selenium status: results of the New Dietary Strategies Addressing the Specific Needs of the Elderly Population for Healthy Aging in Europe (NU-AGE) 1-year randomized clinical trial in elderly Europeans. Issue 1 (26th September 2019) - Jennings, Amy; Tang, Jonathan; Gillings, Rachel; Perfecto, Antonio; Dutton, John; Speakman, Jim; Fraser, William D; Nicoletti, Claudio; Berendsen, Agnes A M; de Groot, Lisette C P G M; Pietruszka, Barbara; Jeruszka-Bielak, Marta; et al.
ABSTRACT: Background: Mediterranean diets limit red meat consumption and increase intakes of high-phytate foods, a combination that could reduce iron status. Conversely, higher intakes of fish, a good source of selenium, could increase selenium status. Objectives: A 1-y randomized controlled trial [New Dietary Strategies Addressing the Specific Needs of the Elderly Population for Healthy Aging in Europe (NU-AGE)] was carried out in older Europeans to investigate the effects of consuming a Mediterranean-style diet on indices of inflammation and changes in nutritional status. Methods: Selenium and iron intakes and status biomarkers were measured at baseline and after 1 y in 1294 people aged 65–79 y from 5 European countries (France, Italy, the Netherlands, Poland, and the United Kingdom) who had been randomly allocated either to a Mediterranean-style diet or to remain on their habitual, Western diet. Results: Estimated selenium intakes increased significantly with the intervention group ( P  < 0.01), but were not accompanied by changes in serum selenium concentrations. Iron intakes also increased ( P  < 0.001), but there was no change in iron status. However, when stratified by study center, there were positive effects of the intervention on iron status for serum ferritin for participants in Italy ( P  = 0.04) and France ( P  = 0.04) and on soluble transferrin receptor (sTfR) for participants in Poland ( P  < 0.01). Meat intake decreased and fish intake increased to a greater degree in the intervention group, relative to the controls ( P  < 0.01 for both), but the overall effects of the intervention on meat and fish intakes were mainly driven by data from Poland and France. Changes in serum selenium in the intervention group were associated with greater changes in serum ferritin ( P  = 0.01) and body iron ( P  = 0.01), but not sTfR ( P  = 0.73); there were no study center × selenium status interactions for the iron biomarkers. Conclusions: Consuming a Mediterranean-style diet for 1 y had no overall effect on iron or selenium status, although there were positive effects on biomarkers of iron status in some countries. The NU-AGE trial was registered at clinicaltrials.gov as NCT01754012.